Meeting the learning needs of diverse students in BSN programs. - Thompson, C (Nurse educator, 1998)
Keywords: *Cultural Diversity; *Education, Nursing, Baccalaureate/mt [Methods]; *Students, Nursing; Cultural Diversity; Education, Nursing, Baccalaureate; Humans; Learning; MLCS; MLOWN; Students, Nursing; article; cultural anthropology; dept.nur; human; learning; methodology; nursing education; nursing student

Critical thinking skills of baccalaureate nursing students at program entry and exit - Thompson, C; Rebeschi, LM (Nursing and Health Care Perspectives, 1999)
Most nurse educators would agree that critical thinking is an essential competency for the professional nurse in today's ever-changing health care environment. In fact, critical thinking has been identified as an integral component of professional nursing practice and has been incorporated in accreditation guidelines (1-3). As a result of this imperative, professional programs of nursing must explicate a clear definition of critical thinking, identify specific learning outcomes reflective of critical thinking abilities, and select appropriate ways to measure the achievement of these outcomes in graduating students. Although much has been written about the need for critical thinking skills, the concept and measurement of critical thinking within the context of nursing education has not yet been clearly defined (4-6). As a result, nursing programs are developing their own conceptual definitions of critical thinking and using a variety of methods to measure outcomes (5). The authors caution that to ensure validity of findings, the instruments used must reflect the individual program's definition of the concept. In most cases, outcomes have been assessed using a cross-sectional design that compares students at different levels or types of programs or are measured as an end-of-program outcome. While such designs can provide educators with knowledge of students' critical thinking abilities at a particular point in the educational process, longitudinal data are needed to assess the effects of the educational program.
Keywords: *Clinical Competence/st [Standards]; *Education, Nursing, Baccalaureate/og [Organization & Administration]; *Educational Measurement/mt [Methods]; *Nursing Process; *Program Evaluation/mt [Methods]; *Students, Nursing/px [Psychology]; *Thinking; Accreditation; Clinical Competence; Education, Nursing, Baccalaureate; Educational Measurement; Humans; Nursing Education Research; Nursing Process; Outcome Assessment (Health Care); Outcome Assessment, Health Care; Program Evaluation; Research Design; Students, Nursing; Thinking; accreditation; article; clinical competence; dept.nur; education; health care quality; human; methodology; nursing education; nursing process; nursing student; organization and management; outcome assessment; psychological aspect; standard; thinking; ⛔ No DOI found

Differences in Classroom Teaching Preferences between Traditional and Adult BSN Students - Thompson, C.; Sheckley, B.G. (Journal of Nursing Education, 1997)
The primary purposes of this study were to identify the best teaching practices for adult baccalaureate (BSN) nursing students and to examine if adult students' teaching preferences differed from those of traditional BSN students. The sample consisted of 206 adult and traditional students in four BSN programs. The adult nursing student sample was further subdivided into two groups: adults with no prior nursing education (adult non-nurses) and adults with prior nursing education (RN'S). Using a two-part, self-administered questionnaire, respondents were asked to rate the frequency with which 41 teaching strategies were used in their best and in their worst classroom learning experiences in nursing. In most cases, adult non-nurses' teaching preferences did not vary significantly from the preferences of traditional students. However, adults with no prior nursing education did show a preference for knowledgeable and organized instructors. In contrast RNs' preferred classroom situations were where time on task was emphasized, cooperative learning was encouraged, and expectations for learning were high. Results indicate that classroom teaching preferences vary as a function of prior experience with the subject matter and are not attributable to age itself. Findings suggest that prior experience with course content is a more important consideration in planning programs than generalized adult experience.
Keywords: *Choice Behavior; *Education, Nursing, Associate; *Education, Nursing, Baccalaureate; *Education, Professional, Retraining; *Students, Nursing/px [Psychology]; *Teaching/st [Standards]; Adolescent; Adult; Choice Behavior; Education, Nursing, Associate; Education, Nursing, Baccalaureate; Education, Professional, Retraining; Factor Analysis, Statistical; Humans; Middle Aged; Nursing Education Research; Questionnaires; Students, Nursing; Surveys and Questionnaires; Teaching; adolescent; adult; article; comparative study; continuing education; decision making; dept.nur; factorial analysis; human; middle aged; nursing education; nursing student; psychological aspect; questionnaire; standard; teaching

Dual assignments: An effective clinical teaching strategy - Gotschall, L.A.; Thompson, C. (Nurse Educator, 1990)
Keywords: dept.nur